Estimation of Natural Variability and Detection of Anthropogenic Signal in Summertime Precipitation over South America - Stefanie Talento; Marcelo Barreiro (Advances in Meteorology)
We use a coupled model to estimate the natural variability of summertime rainfall over South America and to determine the time horizon when anthropogenic forcing will start having an effect on it. We use a combination of three experiments: preindustrial, 20th century, and the projected changes under A1B scenario. The first empirical orthogonal function of rainfall in December–February is used to characterize summertime variability. The model can display two different regimes of natural variability of this mode. In one regime, there is a strong coupling between the South Atlantic convergence zone (SACZ) and the Atlantic Ocean. In the other regime, the SACZ is dominated by internal atmospheric variability. The detection of the impact of anthropogenic forcing is calculated comparing the probability density functions (pdfs) of the preindustrial run with the one under the A1B scenario. We found that the detection strongly depends on the pdf used to characterize internal climate variability. If the pdf of the mode with coupling between the SACZ and the Atlantic Ocean is used, the anthropogenic influence is felt very early within the future scenario (in less than 30 years). On the contrary, with the pdf that characterizes an SACZ dominated by internal atmospheric variability, the forcing is detected only several (almost 50) years into the scenario.